The “Square Box”: Therapeutic Equivalence as a Foundation of the WHO Model List of Essential Medicines - Cappello, Bernadette; Moja, Lorenzo; Figueras, Albert; Magrini, Nicola (Frontiers in Pharmacology, 2020)
Every two years, the World Health Organization (WHO) updates its Model List of Essential Medicines, intended as a guide for countries to adopt or adapt in accordance with local priorities and treatment guidelines, for the development of national essential medicines lists. When more than one therapeutic option is available for a given indication, the WHO Model List often includes a single medicine as representative of a group of equivalent and interchangeable medicines. The representative medicine of that group is listed with an accompanying ‘square box’ symbol. The intended purpose of the square box is to highlight pharmacological classes or groups of medicines for which countries, institutions and health professionals can assume homogeneous therapeutic efficacy and safety and select the most appropriate single medicine based on price, local availability, and acceptability. Though this concept of therapeutic equivalence within a therapeutic class has been endorsed by most authoritative textbooks of pharmacology since Goodman & Gilman’s The Pharmacological Basis of Therapeutics and evidence-based guidelines, marketing forces have often made claims on individual drugs to distinguish them beyond relevant differences shown by reliable evidence: this has generated the concept of “me-too drugs” with its double meaning- i.e., market latecomers differing minimally from products preceding them and whose marketing budgets have significant opportunity costs, or medicines which may be useful to substitute for equivalent products in the event of shortages. The square box concept is applied in the context of a comprehensive list: therapeutic equivalence or interchangeability cannot always be easily established. Different interpretations have been applied to different groups of medicines over the 40+ year history of the Model List. This paper presents the concept of the square box, provides key examples and guidance on how square box listings should be practically interpreted in the development and implementation of national essential medicine lists, considers the applicability of a square box listing concept to biologic medicines and proposes that an updated review of the square box concept and listings is warranted.